Effect of Conjugated Linoleic Acid on Leptin Level: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mohammadi-Sartang, Mohsen; Sohrabi, Zahra; Esmaeilinezhad, Zahra; Aqaeinezhad R, Seyed Mohammad; Jalilpiran, Yahya (Hormone and Metabolic Research, 2018)
The results of human clinical trials examining the effects of conjugated linoleic acid (CLA) on leptin concentration are inconsistent. Our objective was to elucidate the role of conjugated linoleic acid supplementation on leptin through a systematic review and a meta-analysis of available randomized placebo-controlled trials (RCTs). We searched the PubMed, SCOPUS, and ISI web of science up to February2017, in English, to identify RCTs investigating the effect of CLA supplements on plasma leptin concentrations. Weighted mean differences (WMDs) and their respective 95% confidence intervals (CIs) were calculated to assess the efficacy of CLA on leptin concentration by using random effects. Statistical heterogeneity, study quality, meta-regression and publication bias were used based on standard methods. Nineteen RCTs (comprising 26 treatment arms) with 1045 subjects were included in this meta-analysis. Random-effect meta-analysis found a slight but not significant reduction in plasma leptin concentrations (WMD: –0.38 ng/ml, 95% CI: –1.08, 0.32, p=0.286); I2=53.24%, p=0.001), following CLA supplementation. The pooled effect size was robust and remained non-significant in the leave-one-out sensitivity analysis. Subgroup analysis based on BMI status showed that the CLA supplementation significantly reduces leptin when used for obese subjects (WMD: –1.47 ng/ml, 95% CI: –2.15, –0.79, p<0.001) and in the subset of trials lasting<24 weeks of duration (WMD: –0.76 ng/ml, 95% CI: –1.40, –0.12, p=0.019). CLA supplementation might moderately decrease circulatory leptin levels only among obese adults for shorter than 24 weeks. Additional high-quality studies are needed to replicate our results.
Keywords: adipokine; fatty acid; randomization; adipose tissue